2014
DOI: 10.1007/s00592-014-0561-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant of the renin-angiotensin system and prevalence of type 2 diabetes mellitus: a modest but significant effect of aldosterone synthase

Abstract: Recent genome-wide association studies have identified multiple variants that confer risk of type 2 diabetes mellitus (DM). However, established associations explain only a part of the heritability. Thus, even at the genome-wide association studies era, candidate gene approach should be still useful. Recent interventional studies against the renin-angiotensin system (RAS) showed reduction in new onset of DM, implying the system is involved in the onset. We substantiated the hypothesis that genetic variants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Consistently with this observation, Bellili et al found in the general French population that the -344T/C polymorphism was associated with increased risks for incident type 2 diabetes and metabolic syndrome [13]. Similar suggestions were from study of Ichikava et al in which the CT/CC carriers had increased risk of type 2 diabetes by 40% in comparison to TT carriers [30]. Additionally, recent studies have emphasized that the aldosterone synthase CYP11B2 (-344T>C) gene polymorphism may be a useful predictor of the antihypertensive response to valsartan [25,29].…”
Section: Discussionsupporting
confidence: 65%
“…Consistently with this observation, Bellili et al found in the general French population that the -344T/C polymorphism was associated with increased risks for incident type 2 diabetes and metabolic syndrome [13]. Similar suggestions were from study of Ichikava et al in which the CT/CC carriers had increased risk of type 2 diabetes by 40% in comparison to TT carriers [30]. Additionally, recent studies have emphasized that the aldosterone synthase CYP11B2 (-344T>C) gene polymorphism may be a useful predictor of the antihypertensive response to valsartan [25,29].…”
Section: Discussionsupporting
confidence: 65%
“…The rising prevalence has been attributed to sedentary lifestyle related factors; however, genetic predisposition may play a vital role in the etiology and manifestation of the disease [ 3 5 ]. Recently, an ample amount of studies has focused on genetic variants in Renin-Angiotensin-Aldosterone System (RAAS) in association with the components of metabolic syndrome, especially hypertension and T2DM [ 6 8 ]. The association between insulin resistance, hyperinsulinemia, and the RAAS independent of plasma potassium and cortisol levels has been shown [ 9 ] and has been implicated in the development of cardiovascular and renal diseases in T2DM [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The renin-angiotensin system (RAS) plays pivotal roles in blood pressure regulation,[ 1 ] cardiovascular, renal and metabolic conditions[ 2 4 ] and pharmacological status. [ 5 , 6 ] One of the major rate-limiting steps of this system is the conversion of angiotensinogen to angiotensin I, which is catalyzed by renin.…”
Section: Introductionmentioning
confidence: 99%